An investigation of maxillary and mandibular morphology in different overjet groups - Baydaş Bülent; Yavuz İbrahim; Dagsuyu İlhan Metin; Bölükbaşi Berrin; Ceylan İsmail (Sciendo, 2004)
Background: It has been suggested that overjet may be related to the form of the maxilla and mandible.